ANALISIS YURIDIS PENGANGKATAN PENJABAT KEPALA DAERAH SEBAGAI KONSEKUENSI PILKADA SERENTAK 2024 - NIM. A1011201041, JAILANI (Jurnal Fatwa Hukum, 2024)
ABSTRACT  The mention of the position of regional head is a consequence of the regulations in Article 201 Paragraph (9) of Law Number 10 of 2016 concerning the Election of Governors, Regents and Mayors which is the legal basis for appointing the position of regional head. This appointment is a problem that must be researched because apart from the fact that the mechanism for appointing regional head positions is less than democratic, it is also felt that the authority of regional head positions has been controlled by the central government. This research is normative juridical legal research in which data collection was carried out using a case approach, literature review and context. The data sources or legal materials that will be used as a basis to support this research come from primary and secondary data sources or legal materials which are analyzed descriptively. In this research, it was found that the mechanism for placing regional head positions did not meet the principles of democracy to implement the principles of decentralization and regional autonomy as well as the amount of control of the central government through the Minister of Home Affairs, which affected the authority of regional head positions to carry out their duties and authority as they should.The loss of social rights and democratic freedoms is also found in a number of problems caused by the policy of appointing Regional Head Officials, such as weak legitimacy, ongoing regulation of authority, and the lack of guaranteed neutrality of Regional Head Officials from political interests. To overcome this problem, this research provides two recommendations for solutions, namely increasing transparency and implementing democratic values in every mechanism for appointing Regional Head Officials and strengthening the authority related to Regional Head Officials in accordance with the principle of regional autonomy.     Keywords: Appointment of Acting Regional Heads; Mechanism; Authority.   ABSTRAK  Adanya pengangkatan penjabat kepala daerah yang merupakan konsekuensi atas aturan dalam Pasal 201 Ayat (9) Undang-Undang Nomor 10 Tahun 2016 tentang Pemilihan Gubernur, Bupati, dan Walikota yang menjadi dasar hukum pengangkatan penjabat kepala daerah. Pengangkatan tersebut menjadi suatu problematika yang memang harus diteliti karena selain dirasa mekanisme pengangkatan penjabat kepala daerah yang kurang demokratis ditambah lagi kewenangan yang dimiliki penjabat kepala daerah yang dirasa telah ditunggangi oleh pemerintah pusat. Penelitian ini merupakan penelitian hukum yuridis normatif yang mana pengumpulan data dilakukan dengan cara pendekatan kasus, studi kepustakaan, dan konseptual. Adapun sumber data atau bahan hukum yang akan digunakan sebagai dasar untuk menunjang penelitian ini adalah berasal dari sumber data atau bahan hukum  primer dan sekunder yang dianalisis secara deskriptif. Dalam penelitian ini ditemukan bahwa mekanisme pengangkatan penjabat kepala daerah tidak memenuhi prinsip-prinsip demokrasi untuk menyelenggarakan asas desentralisasi dan otonomi daerah serta besarnya kontrol pemerintah pusat melalui Menteri dalam negeri yang membuat terpengaruhinya kewenangan penjabat kepala daerah untuk menjalankan tugas dan wewenang sebagaimana mestinya. Hilangnya hak sosial dan kebebasan berdemokrasi juga ditemukan pada sejumlah permasalahan yang diakibatkan oleh kebijakan pengangkatan Penjabat Kepala Daerah, seperti legitimasi yang lemah, pengaturan kewenangan yang terjadi, dan belum terjaminnya netralitas Penjabat Kepala Daerah dari kepentingan politik. Untuk mengatasi permasalahan tersebut, penelitian ini memberikan dua rekomendasi penyelesaian, yaitu meningkatkan transparansi dan menerapkan nilai-nilai demokrasi dalam setiap mekanisme pengangkatan Penjabat Kepala Daerah serta melakukan penguatan   terkait kewenangan Penjabat Kepala Daerah   sesuai dengan prinsip otonomi daerah.   Kata Kunci : Pengangkatan Penjabat Kepala Daerah; Mekanisme; Kewenangan.